Pulmonary Adenofibroma: Clinicopathological and Genetic Analysis of 7 Cases With Literature Review - Liang, Zuoyu; Zhou, Ping; Wang, Yuxuan; Zhang, Ying; Li, Dan; Su, Xiaoxing; Fan, Yu; Tang, Yuan; Jiang, Lili; Wang, Weiya (Frontiers in Oncology, 2021)
Introduction: Pulmonary adenofibroma (PAF), characterized by biphasic differentiation composed of gland-like space lined by respiratory epithelium and stromal spindle cells, is a rare benign tumor of the lung. PAF was reported infrequently and inconsistently with diagnostic criteria and withstood higher risk of misdiagnosis as solitary fibrous tumors (SFTs) due to their morphological resemblance. In this study, we report seven cases of PAF with gene sequencing results and summarize the data of previous literature. Materials and Methods: Seven cases of PAF with surgically resection samples were collected from Pathology department of West China Hospital, Sichuan University between 2009 to 2020. Immunohistochemical studies were performed in all cases and 3 cases underwent a 425-gene panel next-generation sequencing (NGS). Results: Five female and two male patients were included in this study, with an average age of 51 years. All the patients were asymptomatic, and the lesion was identified on routine chest radiography. The tumor size measured by computed tomography (CT) ranged from 0.5 to 2.7 cm. Gland-like structures were mostly positive for glandular epithelium markers. The spindle cells in stroma expressed Desmin, SMA, ER and PR in 3 of 7 cases. No well-recognized molecular abnormalities can be identified by NGS in the 3 cases. To date, all the patients are alive, with no evidence of recurrence and metastasis. Conclusion: PAF is a unique benign pulmonary tumor with low incidence. Biphasic morphology, IHC stains along with molecular detection is of great significance to make a clear diagnosis.